2017
DOI: 10.1097/iae.0000000000001144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Prognosis and Clinical Features of Cytomegalovirus Retinitis in Hiv and Non-Hiv Patients

Abstract: The overall visual prognosis and the clinical features of CMV retinitis do not differ between HIV and non-HIV patients. The visual prognosis of CMV retinitis still remains quite poor despite advancements in antiviral treatment. This poor prognosis after antiviral treatment is associated with retinal detachment during follow-up, Zone 1 involvement, and the poor general condition of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 21 publications
0
33
1
1
Order By: Relevance
“…CMVR is the most common ocular opportunistic infection and the leading cause of blindness associated with AIDS worldwide [48][49][50][51][52]. CMVR occurs in approximately 20-40% of HIV-infected patients and accounts for 90% of HIV-related blindness [6,20,52]. In the literature to date, the most significant predictor for the development of CMVR is a CD4+ count less than 50 cells/µL [34,46,[53][54][55].…”
Section: Cmvr In Hivmentioning
confidence: 99%
See 3 more Smart Citations
“…CMVR is the most common ocular opportunistic infection and the leading cause of blindness associated with AIDS worldwide [48][49][50][51][52]. CMVR occurs in approximately 20-40% of HIV-infected patients and accounts for 90% of HIV-related blindness [6,20,52]. In the literature to date, the most significant predictor for the development of CMVR is a CD4+ count less than 50 cells/µL [34,46,[53][54][55].…”
Section: Cmvr In Hivmentioning
confidence: 99%
“…As early cases tend to be asymptomatic, symptoms tend to translate into more severe retinitis, early involvement of the macula, or possible infiltration of the optic nerve [48,49]. Kim et al found that the vision at presentation did not significantly differ between the HIV and non-HIV immunosuppressed patients [6]. Lu et al did note worse presenting vision in non-HIV immunosuppressed patients, most likely because their patients were significantly immunocompromised, as the majority of them had hematologic malignancies and had received intensive chemotherapy shortly before presentation [4].…”
Section: Clinical Presentation: Hiv and Non-hiv Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vision loss occurs as a result of posterior pole involvement with retinal necrosis involving the macula or optic nerve, or as a result of complications including retinal detachment (RD), epiretinal membrane (ERM) or cataract [35, 36]. The clinical features of CMVR do not differ between individuals with HIV infection and those with immune compromise from other causes [37]. …”
Section: Clinical Signs and Symptomsmentioning
confidence: 99%